The evolution and maintenance of androdioecy - Pannell, J (2002)
Examples of androdioecy, the coexistence of males and hermaphrodites, was unknown when the subject was last reviewed about two decades ago. Since then, several examples have been discovered in both plants and animals, and we are now in a position to reappraise theoretical work on the subject. Whereas early ideas were framed largely in terms of the invasion of males into hermaphroditic populations, all of the clearest examples of androdioecy now known appear to have evolved from dioecy. There are strong indications that this has occurred repeatedly as a result of the selection of self-fertile hermaphroditism for reproductive assurance during colonization. Male frequencies in these species are highly variable, self-fertilization in hermaphrodites is delayed, and mating opportunities appear to depend strongly on population density. Results from theoretical work on the evolution and maintenance of androdioecy in single populations and in metapopulations are summarized, and several case studies of androdioecious plants and animals are reviewed.